Sharia Banking Transformation through Practices Islamic Corporate Social Responsibility (ICSR) - Ceta Indra Lesmana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The transformation of sharia banking through ICSR practices is an effort to increase competitiveness, customer trust and Islamic values in sharia banking practices. Implementing ICSR can provide significant benefits for sharia banking, customers and society as a whole. The implementation of ICSR practices by sharia banking creates a positive impact in building financial institutions based on Islamic principles. This is not only about building reputation, but also creating strong relationships based on social and moral values, which in turn strengthens integrity and increases customer and community trust. Implementing ICSR can increase the competitiveness of sharia banking by improving product and service quality, positive image and customer trust. Implementing ICSR can also improve customer experience, strengthen relationships between banks and customers, and have a positive impact on society as a whole. Consistent implementation of ICSR can help sharia banking to become more competitive, trusted by customers, and realize Islamic values in banking practices.